2016
DOI: 10.1016/j.ymben.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolic engineering targets for the enhancement of 1,4-butanediol production in recombinant E. coli using large-scale kinetic models

Abstract: Identification of metabolic engineering targets for the enhancement of 1,4-butanediol production in recombinant E. coli using largescale kinetic models, Metabolic Engineering, http://dx.doi.org/10. 1016/j.ymben.2016.01.009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 63 publications
(90 reference statements)
2
73
0
Order By: Relevance
“…By exploiting this property of lumpGEM, we built a reduced model that has an ad hoc defined core with a biomass yield very close to its parent GEM model. With a systematic approach to define the core [48], we can generate representative reduced models that are consistent with their GEM for different studies, such as kinetic modelling [4951], in where it is crucial to base the analysis on models that do not sacrifice stoichiometric, thermodynamic and physiological constraints.…”
Section: Resultsmentioning
confidence: 99%
“…By exploiting this property of lumpGEM, we built a reduced model that has an ad hoc defined core with a biomass yield very close to its parent GEM model. With a systematic approach to define the core [48], we can generate representative reduced models that are consistent with their GEM for different studies, such as kinetic modelling [4951], in where it is crucial to base the analysis on models that do not sacrifice stoichiometric, thermodynamic and physiological constraints.…”
Section: Resultsmentioning
confidence: 99%
“…The resultant model, consisting of a series of classification rules built by a decision tree algorithm, found that only 27 out of the 153 potential enzymes had narrow ranges of feasible kinetic parameters. Presumed to be critical to product formation, a population of 200 000 + ORACLE models was generated in a follow‐up study to examine the effects of these 27 enzymes on predicted BDO production . While not tested in vivo in this study, the enzymes the model population suggested to be the most critical influencers of BDO production were consistent with what was seen in previous experimental studies.…”
Section: Review Of Instances Of Data‐driven Me Effortssupporting
confidence: 55%
“…2; Additional file 2). This implies that for all the enzymes in the network their control over fluxes and concentrations would depend on their kinetic properties and saturation state [33, 35, 38]. We assumed that the reaction catalyzed by malic enzyme (MAE) was operating in the direction of decarboxylation because it has been observed that pyruvate carboxylase-negative strains of S. cerevisiae are not capable of growing on glucose indicating that MAE cannot assume the anaplerotic role of pyruvate carboxylase [39].…”
Section: Resultsmentioning
confidence: 99%